Human Scenes : International Seminar on Photography Alden Biesen 1991. - Swinnen, Johan; Landcommanderij Alden Biesen, Bilzen (Genk : Aksent, 1991)
Burns, Marsha ; Carlier, Jan ; Claass, Arnaud ; Hansen, Ben ; Michals, Duane ; Vogt, Christian
Losse bladzijden per kunstenaar
Landcommancerij, Alden Biesen, 1991
kunstcatalogus